2020
DOI: 10.1101/2020.11.29.20214544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preferences and barriers to mental help seeking among students attending the University of Dschang, West region, Cameroon

Abstract: Background: Mental disorders are a major source of disability and receive little attention in developing countries in general and particularly in Cameroon. Students are at a higher risk of developing mental disorders. The aim of this study was to assess students mental help seeking preferences and the barriers to mental health seeking. Methods: We conducted a cross sectional study. Participants were selected using a multistage sampling method. A self-administered questionnaire was used to collect data on socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A recurring perception that emerged was the stigma that if someone sees a psychologist, then it meant that they were mentally disturbed. Additionally, a study by Martial et al (2020) found that only 38.3 percent of the students were willing to seek help from a psychologist on campus while the majority about 50.2 percent preferred a private hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A recurring perception that emerged was the stigma that if someone sees a psychologist, then it meant that they were mentally disturbed. Additionally, a study by Martial et al (2020) found that only 38.3 percent of the students were willing to seek help from a psychologist on campus while the majority about 50.2 percent preferred a private hospital.…”
Section: Introductionmentioning
confidence: 99%